Bio-based polycarbonate copolymer and preparation method thereof
By copolymerizing isosorbide with amide diol and crystallizable oligomer diol, the problem of increasing the glass transition temperature of isosorbide-based polycarbonate while maintaining high strength, high toughness and high transparency was solved, and the preparation of high-performance bio-based polycarbonate copolymers was achieved.
Patent Information
- Application Number
- CN202510748899.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2025-10-17
AI Technical Summary
It is difficult to increase the glass transition temperature of isosorbide-based polycarbonate while maintaining high strength, high toughness and high transparency in existing technologies, and existing modification methods will lead to performance degradation.
Bio-based polycarbonate copolymers are prepared by copolymerizing isosorbide with amide diols and crystallizable oligomeric diols. Amide diols are introduced to increase polarity, and crystallizable oligomeric diols such as polycaprolactone diol are used to increase molecular weight and chain length. The molar ratio and reaction conditions are adjusted to optimize performance.
A high-performance bio-based polycarbonate copolymer was prepared with a tensile strength of not less than 70 MPa, an elongation at break of not less than 70%, a glass transition temperature of not less than 130°C, a light transmittance of not less than 90%, and a pencil hardness of not less than 2H.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of new materials, and particularly relates to a bio-based polycarbonate copolymer and a preparation method thereof. BACKGROUND
[0002] Bisphenol A polycarbonate (BPA-PC) has excellent comprehensive performance, and is widely used in the fields of electronic appliances, food packaging, building materials and medical devices. However, studies have shown that the main raw material of BPA-PC, bisphenol A, has slow toxicity and estrogen effect, which may endanger human health, so it is of great significance to find a bio-based raw material to replace bisphenol A to prepare high-performance green and non-toxic polycarbonate.
[0003] Isosorbide is a rigid double heterocyclic diol derived from a bio-based sugar, and has a similar chemical structure to bisphenol A, and is considered to be the most potential bio-based raw material to replace bisphenol A to prepare polycarbonate. However, due to the large number of rigid isosorbide groups in the main chain structure of isosorbide-based polycarbonate, the glass transition temperature is high, and the plasticity is poor and it is difficult to be processed and molded, so it is necessary to modify the isosorbide-based polycarbonate to improve its plasticity and processability.
[0004] Currently, the chemical modification of isosorbide-based polycarbonates is mostly copolymerized with flexible small molecule diols to prepare isosorbide-based polycarbonate polymers. With the increase of the content of flexible diols, the plasticity and toughness increase, but the strength and glass transition temperature decrease significantly, which greatly limits its application in the field of engineering plastics. For example, the paper "Green and Efficient Synthesis of Biobased Polycarbonates with Tunable Performance via Functionalized Ionic Liquid Catalysts Enhanced by Cation-π Interactions" (https: / / doi.org / 10.1021 / acs.iecr.4c00480) copolymerizes isosorbide with 1,10 decanediol to prepare isosorbide-based polycarbonate copolymer. The incorporation of soft comonomer improves the ductility and processability of isosorbide-based polycarbonate, and the elongation at break increases from 34% to 358%, and the tensile strength decreases from 63.6 MPa to 36.7 MPa, but the glass transition temperature decreases from 99℃ to 43℃. For example, the paper "Synthesis of Thermal-Resistant Polyester-Polycarbonate with Fully Rigid Structure from Biobased Isosorbide" (https: / / doi.org / 10.1021 / acs.macromol.4c00647) prepared isosorbide-based polyester-polycarbonate copolymer by melt transesterification of isosorbide, dimethyl terephthalate, 1,4-cyclohexane dimethanol and dimethyl carbonate. By adjusting the ratio of isosorbide and 1,4-cyclohexane dimethanol, the flexibility of isosorbide-based polycarbonate is successfully increased, and the elongation at break reaches 136%. However, the glass transition temperature decreases to 76℃, and the significant increase of the fracture strain is accompanied by a sharp decrease of the glass transition temperature. Therefore, the addition of flexible small molecules is not conducive to the preparation of a biobased polycarbonate copolymer with high strength, high toughness, high transparency and high glass transition temperature.
[0005] Patent CN 105237755 A discloses a copolymer carbonate with low water absorption, excellent heat resistance, low temperature characteristics and surface hardness, but the present invention finds that its related properties, such as glass transition temperature, light transmittance and pencil hardness, still have room for improvement. SUMMARY
[0006] TECHNICAL PROBLEM
[0007] The plasticity, toughness, strength and glass transition temperature cannot be well coordinated when preparing polycarbonate using isosorbide, and thus a preparation method of a high-strength, high-toughness and high-transparency bio-based polycarbonate copolymer with high glass transition temperature is needed.
[0008] Technical content
[0009] In view of the above problems in the prior art, the present application provides a high-performance bio-based polycarbonate copolymer and a preparation method thereof. The bio-based polycarbonate copolymer is prepared by copolymerizing isosorbide with amide diol and crystallizable oligomer diol, and has high strength, high toughness and high transparency, and high heat resistance. It is a very potential bio-based engineering plastic.
[0010] The first object of the present application is to provide a high-performance bio-based polycarbonate copolymer, which has a tensile strength of not less than 70 MPa, an elongation at break of not less than 70%, a light transmittance of not less than 90%, a glass transition temperature of not less than 130℃, a pencil hardness of not less than 2H, and a relative weight average molecular weight of 6×10 4 -2×10 5
[0011] Further, the molecular chain of the bio-based polycarbonate copolymer is composed of the following structural units: -ORCOO-, -OR1COO- and -OR2COO- groups.
[0012] Further, R is isohexide C6H8O2.
[0013] Further, R1 is (C6H 10 O2) x ·OR3 or (C6H 10 O2) x ·R3, x = 4-8.
[0014] Further, R2 is C4H 10 O2(N)COR4.
[0015] Further, R3 and R4 are selected from alkane containing 2-15 C atoms.
[0016] Further, the number ratio between -ORCOO- and -OR1COO- groups is 1:0.03-0.07.
[0017] Further, the number ratio between -ORCOO- and -OR2COO- groups is 1:0.01-0.04.
[0018] A second object of the present application is to provide the use of the high-performance bio-based polycarbonate copolymer in the field of electronic appliances, food packaging, building materials, containers, vehicles, engineering plastics or medical devices.
[0019] A third object of the present application is to provide a preparation method of the high-performance bio-based polycarbonate copolymer, comprising the following steps:
[0020] (1) heating and melting isosorbide, crystallizable oligomer diol, amide diol and carbonic acid diester under a protective atmosphere, and then adding a catalyst to react;
[0021] (2) increasing the reaction temperature to 200-280℃ under a low vacuum condition, and maintaining the reaction time for 0.2h-5h to obtain the high-performance isosorbide-based polyester-polycarbonate copolymer.
[0022] Further, the protective atmosphere in step (1) comprises nitrogen and / or inert gas.
[0023] Further, the isosorbide in step (1) can be replaced by its isomer with the molecular formula of C6H 10 O4.
[0024] Further, the crystallizable oligomer diol in step (1) is a homopolymer diol of 2-oxepanone.
[0025] Further, the crystallizable oligomer diol in step (1) is specifically polycaprolactone diol.
[0026] Further, the molecular weight of the crystallizable oligomer diol in step (1) is 500-800.
[0027] Further, the amide diol in step (1) is at least one selected from N,N-bis(2-hydroxyethyl)acetamide, N,N-bis(2-hydroxyethyl)propionamide, N,N-bis(2-hydroxyethyl)butyramide, N,N-bis(2-hydroxyethyl)valeramide, N,N-bis(2-hydroxyethyl)hexanamide, N,N-bis(2-hydroxyethyl)heptanamide and N,N-bis(2-hydroxyethyl)octanamide.
[0028] Further, the preparation process of the amide diol is as follows: stirring diethanolamine and fatty acid methyl ester under a nitrogen atmosphere, adding a catalyst to react, and then extracting and purifying the reaction product to obtain the amide diol.
[0029] In an embodiment of the present application, the molar ratio of diethanolamine to fatty acid methyl ester is 1:0.8-1.2.
[0030] In an embodiment of the present application, the fatty acid methyl ester comprises any one of methyl formate, methyl acetate, methyl propionate, methyl butyrate, methyl valerate, methyl hexanoate and methyl heptanoate.
[0031] In an embodiment of the present application, the catalyst is sodium methoxide.
[0032] In an embodiment of the present application, the molar ratio of diethanolamine to catalyst is 1:0.005-0.01.
[0033] In an embodiment of the present application, the reaction temperature is 20-25°C and the reaction time is 20-30 hours.
[0034] In an embodiment of the present application, the extraction and purification process comprises washing with saturated brine, drying with anhydrous magnesium sulfate and rotary evaporation.
[0035] Further, the carbonic acid diester in step (1) is selected from one of diphenyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate and dibutyl carbonate.
[0036] Further, the molar ratio of isosorbide to the crystallizable oligomeric diol is 1:0.03-0.1.
[0037] Further, the molar ratio of isosorbide to the amide diol is 1:0.01-0.05.
[0038] Further, the molar ratio of isosorbide to the carbonic acid diester is 1:1-10.
[0039] Preferably, the molar ratio of isosorbide to the carbonic acid diester is 1:1-5.
[0040] More preferably, the molar ratio of isosorbide to the carbonic acid diester is 1:1-2.
[0041] Further, the temperature for heating and melting in step (1) is 90-150°C.
[0042] Further, the catalyst in step (1) is at least one of a metal catalyst, a basic catalyst and an ionic liquid catalyst.
[0043] Further, the metal catalyst is one of lithium acetylacetonate, lithium lactate and cesium carbonate.
[0044] Further, the basic catalyst is one of 1,5,7-triazabicyclo[4.4.0]dec-5-ene and 4-dimethylaminopyridine.
[0045] Further, the ionic liquid catalyst is one of 1-ethyl-3-methylimidazolium lactate and 1-butyl-3-methylimidazolium lactate.
[0046] Preferably, the catalyst in step (1) is selected from one of 1-butyl-3-methylimidazolium lactate, lithium acetylacetonate, lithium lactate and 1-ethyl-3-methylimidazolium lactate.
[0047] Further, the catalyst in step (1) is added in a molar amount of 0.005-0.01% of the molar amount of the carbonic acid diester.
[0048] Further, the reaction time in step (1) is 1-5 hours.
[0049] Further, the low vacuum condition in step (2) refers to a condition with a vacuum degree less than 100 Pa.
[0050] Further, the low vacuum condition in step (2) refers to a condition with a vacuum degree of 10-100 Pa.
[0051] The beneficial effects of the present application are:
[0052] 1. Compared with the prior art, the present application introduces amide diol, which can increase the polarity of the obtained polymer molecules, effectively enhance the strength and heat resistance of the polymer, and endow the polymer with better flexibility.
[0053] 2. Compared with the prior art, the present application selects a crystallizable oligomer diol (polycaprolactone diol, Mn=500-800), which has a longer chain segment and a higher molecular weight than small molecule diol, so that a higher molecular weight polycarbonate copolymer can be more easily prepared, and the crystallizable oligomer diol has a polar ester group, which can endow the main chain with higher tensile strength and glass transition temperature, and the long alkane segment in the crystallizable oligomer diol can effectively increase the elongation at break and toughness of the bio-based polycarbonate copolymer.
[0054] 3. The present application effectively regulates the molecular weight and feeding molar amount of the crystallizable oligomer diol to prepare a bio-based polycarbonate copolymer with high tensile strength, excellent anti-fracture performance and high glass transition temperature, which has a tensile strength of 70-80 MPa, an elongation of 70-100%, and a glass transition temperature of 130-140°C. DETAILED DESCRIPTION
[0055] The present application is described in detail below with reference to examples. The raw materials used in the examples are commercially available unless otherwise specified. The purity of isosorbide is greater than 98%, the purity of diphenyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate and dibutyl carbonate is 99%, the purity of 2-oxepanone homopolymer diol (PCL diol) is 99%, and the purity of lithium acetylacetonate, lithium lactate, cesium carbonate, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 4-dimethylaminopyridine, 1-ethyl-3-methylimidazolium lactate and 1-butyl-3-methylimidazolium lactate is 99%.
[0056] N,N-bis(2-hydroxyethyl)acetamide, N,N-bis(2-hydroxyethyl)propionamide, N,N-bis(2-hydroxyethyl)butyramide, N,N-bis(2-hydroxyethyl)valeramide, N,N-bis(2-hydroxyethyl)hexanamide, N,N-bis(2-hydroxyethyl)heptanamide and N,N-bis(2-hydroxyethyl)octanamide are prepared by synthesis, and the specific preparation process is as follows:
[0057] For example, N,N-bis(2-hydroxyethyl)acetamide is prepared by stirring 2.1 g of diethanolamine with 1.213 g of methyl formate under a nitrogen atmosphere at room temperature, adding 6 mg of sodium methoxide as a catalyst, and continuing the reaction for 24 h. Then, the reaction product is dissolved in an appropriate amount of dichloromethane, washed with saturated brine for 3 times, dried with anhydrous magnesium sulfate, and finally obtained by rotary evaporation.
[0058] Similarly, N,N-bis(2-hydroxyethyl)propionamide, N,N-bis(2-hydroxyethyl)butyramide, N,N-bis(2-hydroxyethyl)valeramide, N,N-bis(2-hydroxyethyl)hexanamide, N,N-bis(2-hydroxyethyl)heptanamide and N,N-bis(2-hydroxyethyl)octanamide are prepared by reacting diethanolamine with equal molar amounts of methyl acetate, methyl propionate, methyl butyrate, methyl valerate, methyl hexanoate and methyl heptanoate, respectively, according to the above preparation process.
[0059] Detection process
[0060] Gel permeation chromatography: 5 mg of sample is dissolved in 2 mL of spectroscopic grade N,N-dimethylformamide, filtered using a 0.22 μm organic filter, and tested using an Agilent 1260 GPC at a flow rate of 1 mL / min, with N,N-dimethylformamide as the mobile phase and polystyrene as the standard.
[0061] Mechanical properties: The sample is cut into dumbbell-shaped samples with a width of 4 mm, a thickness of 0.5 mm and a length of 18 mm. The Instron 5967X dual-column benchtop testing system is used to stretch the sample at a rate of 10 mm / min at room temperature. Five samples are taken for each sample, the average value is calculated and the error is calculated.
[0062] Glass transition temperature: The glass transition temperature of the sample was tested using Mettler DSC 3, 10 mg sample was put into an aluminum crucible, first heated from 30 to 200 °C at 30 °C / min, held for 1 min, then cooled from 200 to -20 °C at 30 °C / min, held for 1 min, and finally heated from 30 to 200 °C at 10 °C / min, and the inflection point was taken as its glass transition temperature.
[0063] Transmittance: The transmittance was tested using Shimadzu UV-3600plus from 400-800 nm, the sample thickness was 0.2 mm, and the transmittance was taken from the data at 550 nm.
[0064] Pencil hardness: The pencil hardness was tested using Shanghai Posh BY Pencil Hardness Instrument according to the national standard GBT 6739-2006.
[0065] Example 1
[0066] 11.035 g of isosorbide, 17.31 g of diphenyl carbonate, 2.12 g of PCL diol (Mn = 530), and 0.294 g of N,N-bis(2-hydroxyethyl)acetamide were added to a three-necked flask, heated at 135 °C under N2 atmosphere, after the raw materials were melted, 1 mg of 1-butyl-3-methylimidazolium lactate was added, and the ester exchange process was carried out for 4 h under mechanical stirring; then the nitrogen was turned off and the vacuum degree was adjusted to 80 Pa, and then the temperature was continuously increased to 250 °C for the polycondensation process, and the reaction was stopped after 0.5 h to obtain the copolymer, with a yield of 98%, and the weight average molecular weight of the product was 112500.
[0067] The mechanical properties and thermal properties of the copolymer are shown in Table 1.
[0068] Example 2
[0069] The same as Example 1, 1-butyl-3-methylimidazolium lactate was replaced by equimolar lithium acetylacetonate, and other conditions were unchanged, to obtain the copolymer, with a yield of 94%, and the weight average molecular weight of the product was 96400.
[0070] Example 3
[0071] The same as Example 1, 1-butyl-3-methylimidazolium lactate was replaced by equimolar lithium lactate, and other conditions were unchanged, to obtain the copolymer, with a yield of 92%, and the weight average molecular weight of the product was 89600.
[0072] Example 4
[0073] The same as Example 1, 1-butyl-3-methylimidazolium lactate was replaced by equimolar cesium carbonate, and other conditions were unchanged, to obtain the copolymer, with a yield of 89%, and the weight average molecular weight of the product was 85300.
[0074] Example 5
[0075] Example 5
[0076] Example 6
[0077] Example 6
[0078] Example 7
[0079] Example 7
[0080] Example 8
[0081] Example 8
[0082] Example 9
[0083] Example 9
[0084] Example 10
[0085] Example 10
[0086] Example 11
[0087] The same as Example 1, the raw materials are replaced by 11.035 g of isosorbide, 17.31 g of diphenyl carbonate, 2.12 g of PCL diol (Mn = 530) and 0.519 g of N,N-bis(2-hydroxyethyl)decanamide, the catalyst is replaced by an equimolar amount of lithium acetylacetonate, and the other conditions remain unchanged, to obtain a copolymer with a yield of 94% and a weight average molecular weight of the product of 96500.
[0088] Comparative Example 1
[0089] 11.035 g of isosorbide, 17.31 g of diphenyl carbonate and 2.4 g of PCL diol (Mn = 400) were added to a three-necked flask, 1 mg of 1-butyl-3-methylimidazolium lactate was added after melting at 135°C under N2 atmosphere, mechanical stirring for 4 h, then the nitrogen was turned off and the vacuum degree was adjusted to 80 Pa, and then the temperature was continuously increased to 250°C, the reaction was stopped after 0.5 h to obtain a copolymer with a yield of 96% and a weight average molecular weight of the product of 104600.
[0090] Comparative Example 2
[0091] 11.035 g of isosorbide, 17.31 g of diphenyl carbonate and 3.18 g of PCL diol (Mn = 530) were added to a three-necked flask, 1 mg of 1-butyl-3-methylimidazolium lactate was added after melting at 135°C under N2 atmosphere, mechanical stirring for 4 h, then the nitrogen was turned off and the vacuum degree was adjusted to 80 Pa, and then the temperature was continuously increased to 250°C, the reaction was stopped after 0.5 h to obtain a copolymer with a yield of 97% and a weight average molecular weight of the product of 116600.
[0092] Comparative Example 3
[0093] The same as Comparative Example 1, the raw materials are replaced by 11.035 g of isosorbide, 17.31 g of diphenyl carbonate and 4.98 g of PCL diol (Mn = 830), and the other conditions remain unchanged, to obtain a copolymer with a yield of 96% and a weight average molecular weight of the product of 119900.
[0094] Table 1 Performance comparison of examples and comparative examples
[0095] Tensile strength / MPa Elongation at break / % Glass transition temperature / °C Transmittance / % Pencil hardness Example 1 Example 2 80±4 80±3 140 90.8 3H Example 3 76±5 70±4 138 90.5 3H Example 4 76±3 70±3 137 90.6 3H Example 5 75±3 65±5 136 90.5 3H Example 6 72±3 60±4 136 90.3 2H Example 7 70±4 60±3 135 90.4 2H Example 8 78±3 72±5 138 90.2 3H Example 9 76±3 75±5 136 90.0 3H Example 10 76±4 85±5 135 90.1 2H Example 11 75±2 95±5 132 90.0 2H Comparative Example 1 73±3 100±6 130 89.9 2H Comparative Example 2 74±5 50±2 125 89.5 2H Comparative Example 3 70±3 70±4 120 89.6 H HB 62±3 120±8 105 86.6
[0096] According to the data in Table 1, it can be seen that the glass transition temperature, light transmittance and pencil hardness of the copolymer prepared by the embodiment of the present application are generally more superior than those of the copolymer of the comparative example, which indicates that the introduction of amide diol can increase the polarity of the polymer molecules, effectively enhance the strength and heat resistance of the polymer, achieve a higher glass transition temperature and pencil hardness, and the alkane chain on the side chain of the amide diol can effectively improve the flexibility of the polymer. At the same time, the selection of polycaprolactone diol with a molecular weight of 500-800 is also the key to realizing the performance improvement of the copolymer.
[0097] In addition, in the data comparison of Examples 1-7, it can be found that the elongation at break of the copolymer prepared by using different catalysts is different, and the effect of 1-ethyl-3-methylimidazole lactate, lithium acetylacetonate and lithium lactate is better.
[0098] The above provided examples are not intended to limit the scope covered by the present application, and the described steps are not intended to limit the execution order. The improvements of the present application made by those skilled in the art in combination with the existing common knowledge are also within the protection scope defined by the claims of the present application.
Claims
1. A high-performance bio-based polycarbonate copolymer, characterized in that: Its molecular chain contains the following structural units: -ORCOO-, -OR1COO- and -OR2COO- groups; Where R is C6H8O2, R1 is [(C6H 10 O2) x OC4H8 or (C6H 10 O2) x ·R3], R2 is [C4H 10 O2(N)COR4], R3 and R4 are selected from at least one alkane containing 2-15 C atoms, and x=4-8; The quantitative ratio among -ORCOO-, -OR1COO- and -OR2COO- groups is 1:0.03-0.07:0.01-0.
04.
2. A method for preparing the bio-based polycarbonate copolymer according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Under a protective gas atmosphere, isosorbide, a crystallizable oligomer diol, an amide diol, and a carbonate diester are heated and melted, and then a catalyst is added to react; The oligomer diol is a homopolymer diol of 2-oxepanone with a molecular weight of 500 to 800; the molar ratio of isosorbide to the crystallizable oligomer diol is 1:0.03 to 0.1; the molar ratio of isosorbide to the amide diol is 1:0.01 to 0.05; and the molar ratio of isosorbide to the carbonate diester is 1:1 to 10; The catalyst is one of lithium acetylacetonate, lithium lactate, cesium carbonate, 1,5,7-triazabicyclo[4.4.0]decene-5-ene and 4-dimethylaminopyridine, 1-ethyl-3-methylimidazole lactate and 1-butyl-3-methylimidazole lactate; the molar amount of the catalyst added is 0.005-0.01% of the molar amount of the carbonate diester; (2) Raising the reaction temperature to 200-280° C. under low vacuum conditions and continuing the reaction time for 0.2 h to 5 h to obtain a high-performance isosorbide-based polyester-polycarbonate copolymer.
3. The preparation method according to claim 2, characterized in that In step (1), isosorbide is replaced by other compounds with the molecular formula C6H 10 Isomers of O4.
4. The preparation method according to claim 2, characterized in that In step (1), the amide diol is selected from at least one of N,N-bis(2-hydroxyethyl)acetamide, N,N-bis(2-hydroxyethyl)propionamide, N,N-bis(2-hydroxyethyl)butyramide, N,N-bis(2-hydroxyethyl)valeramide, N,N-bis(2-hydroxyethyl)hexanamide, N,N-bis(2-hydroxyethyl)heptylamide and N,N-bis(2-hydroxyethyl)octanamide.
5. The preparation method according to claim 2, characterized in that In step (1), the carbonic acid diester is selected from one of diphenyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate and dibutyl carbonate.
6. The preparation method according to claim 2, characterized in that The heating and melting temperature in step (1) is 90 to 150°C.
7. The preparation method according to claim 2, characterized in that In step (1), the catalyst is selected from one of 1-butyl-3-methylimidazole lactate, lithium acetylacetonate, lithium lactate and 1-ethyl-3-methylimidazole lactate.
8. The preparation method according to claim 2, characterized in that The reaction time in step (1) is 1 to 5 hours.
9. The preparation method according to claim 2, characterized in that The low vacuum condition in step (2) refers to a condition where the vacuum degree is less than 100 Pa.
10. Use of the bio-based polycarbonate copolymer according to claim 1, or the bio-based polycarbonate copolymer prepared by the preparation method according to any one of claims 2 to 9, in the fields of electronic appliances, food packaging, building materials, containers, vehicles, engineering plastics or medical devices.
Citation Information
Patent Citations
Copolycarbonate
CN105237755A
Novel polycarbonate block amide copolymer as well as preparation method and application of polycarbonate block amide copolymer
CN106589342A
Isosorbide polycarbonate and preparation method thereof
CN114957640A
Polyolefin-like bio-based linear polyesteramide and preparation method thereof
CN115286788A
Cited By
Bio-based flexibilizer modified isosorbide polycarbonate and preparation method thereof
CN122302528A
